PENGARUH MEDIA PEMBELAJARAN BERBASIS CANVA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA SISWA KELAS XI BISNIS DIGITAL SMK SWASTA BUDI AGUNG - Andri Pramana; Dita Eka Pertiwi Sirait (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of Canva-based learning media and learning motivation on the learning outcomes of Grade XI students at Budi Agung Vocational High School, Digital Marketing Program. This research employed a quantitative approach with a sample of 31 students. Data were collected through questionnaires and documentation, while data analysis was conducted using multiple linear regression analysis. The results showed that Canva-based learning media had a positive and significant effect on students’ learning outcomes with a coefficient of 0.606. Learning motivation also had a positive and significant effect on learning outcomes with a coefficient of 0.867. Simultaneously, Canva-based learning media and learning motivation had a significant effect on students’ learning outcomes. The coefficient of determination (R²) of 0.805 indicates that 80.5% of the variation in learning outcomes can be explained by these two variables, while the remaining 19.5% is influenced by other factors outside the scope of this study. Based on these findings, it can be concluded that the use of Canva-based digital learning media and the enhancement of learning motivation are effective strategies for improving students’ learning outcomes in Digital Marketing subjects.